Analysis of Mammalian Native Elongating Transcript sequencing (mNET-seq) high-throughput data - Prudêncio, Pedro (2020)
Fundação para a Ciência e Tecnologia (FCT)/ Ministério da Ciência, Tecnologia e Ensino Superior (MCTES) through Fundos do Orçamento de Estado (UID/BIM/50005/2019), and FCT/FEDER/POR Lisboa 2020, Programa Operacional Regional de Lisboa, PORTUGAL 2020 (LISBOA-01-0145-FEDER-016394).. R.G.M. is supported by FCT grants PTDC/BEX-BID/0395/2014 , PTDC/BIA-BID/28441/2017